ANALISIS INTERAKSI EDUKATIF ANTARA GURU DAN SISWA PADA PROSES PEMBELAJARAN SOSIOLOGI DI SMA - Asvitaria, Asvitaria; Budjang A, Gusti; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to know the educative interaction between teacher and students of class XI IPS in the process of learning sociology in SMA Santun Untan Pontianak. The approach was qualitative approach with descriptive method. The techniques of data collection are used observation techniques , interviews, and documentation studies,with data collection such as obsrevation. The analysis of this researchs is presented descriptive qualitative with five informants that consisting of one teacher of sociology subject of class XI IPS, and four students of class XI IPS.The result shows educative interaction between teacher and student at the time of study of socilogy applied on three processes. The first process at the opening of the lesson prosess is done by attracting student’s attantion, motivating students giving reference / learning structures, linking topics already mastered to new topics and responding to student situations. The second process when describing the material is done by conveying information, explaning, motivating, making personal opinions. And a third process at closing learning is done by summarizing the main points of the lesson, giving psychological / sociological encoragement, giving directions for the next lesson, and evaluating. Keywords: Educational interaction, Teachers, Students, Sociology Learning